Penatalaksanaan Fisioterapi pada Kasus Low Back Pain Myogenic e.c. Lumbar Strain di RSUD Panembahan Senopati Bantul - Abdullah, M. Said, Yulisna Mutia Sari., SSt. FT, Msc. (GRS) (2015)
Backgound: Pain at lumbar spine region commonly described as low back pain.. Pain at this region will cause muscle spasm that wil cause ROM restriction. In this case, myogenic low back pain described as back pain that only caused by muscle disorder without neurological disorder. Aims: To evaluate physical therapy management to pain, muscle spasm, improvement range of motion, and functional activity on low back pain myogenic e.c. lumbar strain. Result: After 7 times of physical therapy management. We found decresing of pain T1: mild pain to T7: no pain, muscle spasm T1: 100% to T7: 30%, flexion tunk range of motion T1: 2 cm to T7: 2,5 cm, right side flexion T1: -50 cm menjadi T7: -47 cm, left side flexion T1: 51 cm to T7: 48,5 cm, functional activity T1: -32% to T7: -30 %. Conclusion: Physical Therapy management with SWD, stretching, massage, core stability exercise can decrease pain, spasm, improve ROM, and enhance functional activity. Keywords: Lumbar strain, Short Wave Diathermy (SWD), massage, stetching, core stability exercise.